2019
DOI: 10.1016/j.poly.2019.04.029
|View full text |Cite
|
Sign up to set email alerts
|

N3O6 versus N2O6 coordinated dysprosium slow magnetic relaxation in a tetrathiafulvalene-based dinuclear complex

Abstract: The reaction between the 2-(1-(4'-[4-(methylphenyl]-2,2:6',2''-terpyridyl)-4,5-(4,5bis(propylthio)-tetrathiafulvalenyl)-1H-benzimidazol-2-yl)-pyridine (L) and 2 equivalents of Dy(hfac) 3 2H 2 O (hfac-= 1,1,1,5,5,5-hexafluoroacetyacetonate) metallic precursors leads to the formation of a dinuclear complex of formula [Dy 2 (hfac) 6 (L)]C 6 H 14 (Dy2). The X-ray structure on single crystal reveals the occupation of the two benzoimidazolylpyridine (bzip) and terpyridyl (terpy) coordination sites with a Dy(III) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The presence of multiple out-of-phase magnetic susceptibility contributions could be attributed to Ln(III) ions in different coordination environments 74,75 crystallographically independent Ln III ions, 76 or to the presence of significant dipolar interaction. 77 The latter origin could be discarded because the ac magnetic susceptibility was carried out under an applied dc field.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…The presence of multiple out-of-phase magnetic susceptibility contributions could be attributed to Ln(III) ions in different coordination environments 74,75 crystallographically independent Ln III ions, 76 or to the presence of significant dipolar interaction. 77 The latter origin could be discarded because the ac magnetic susceptibility was carried out under an applied dc field.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…with the 2,6-di(pyrazol-1-yl)-4-(bromomethyl)pyridine [138,139] and 4'-[4-(bromomethyl)phenyl]-2,2:6',2"-terpyridine [140] using similar procedure than for L 4 . Once they reacted with two equivalents of Dy(hfac)32H2O precursors, dinuclear complexes were obtained and isolated as single crystals with the formula [Dy2(hfac)6(L 5 )](CH2Cl2)2C6H14 ( 7) [141] and [Dy2(hfac)6(L6)]C6H14 (8) [142] (Figure 12). The two structures confirmed that the two bis-and trischelating coordination sites are occupied by the Dy(hfac)3 moieties with distinct coordination sphere symmetry.…”
Section: Auto-assembly Of Single-molecule Magnetmentioning
confidence: 99%
“…The ligands 2‐(1‐(2,6‐di(pyrazol‐1‐yl)‐4‐methylpyridyl)‐4,5‐(4,5‐bis(propylthio)‐tetrathiafulvalenyl)‐1H‐benzimidazol‐2‐yl)‐pyridine ( L 5 ) and 2‐(1‐(4′‐[4‐(methylphenyl)]‐2,2:6′,2′′‐terpyridyl)‐4,5‐(4,5‐bis(propylthio)‐tetrathiafulvalenyl)‐1H‐benzimidazol‐2‐yl)‐pyridine ( L 6 ) (Scheme ) were obtained by alkylation of L 1 with the 2,6‐di(pyrazol‐1‐yl)‐4‐(bromomethyl)pyridine, and 4′‐[4‐(bromomethyl)phenyl]‐2,2:6′,2′′‐terpyridine using similar procedure than for L 4 . Once they reacted with two equivalents of Dy(hfac) 3 · 2H 2 O precursors, dinuclear complexes were obtained and isolated as single crystals with the formula [Dy 2 (hfac) 6 ( L 5 )] · (CH 2 Cl 2 ) 2 · C 6 H 14 ( 7 ) and [Dy 2 (hfac) 6 (L 6 )] · C 6 H 14 ( 8 ) (Figure ).…”
Section: Auto‐assembly Of Single‐molecule Magnetsmentioning
confidence: 99%
“…Color code: carbon: gray, nitrogen: blue, oxygen: red, sulfur: yellow, fluoride: light green and dysprosium: light blue. Adapted from refs , …”
Section: Auto‐assembly Of Single‐molecule Magnetsmentioning
confidence: 99%
See 1 more Smart Citation